Dabrafenib and Trametinib Therapy for Advanced Anaplastic Thyroid Cancer – Real-World Outcomes From UK Centres. Issue 1 (January 2023) - Lorimer, C.; Cheng, L.; Chandler, R.; Garcez, K.; Gill, V.; Graham, K.; Grant, W.; Sardo Infirri, S.; Wadsley, J.; Wall, L.; Webber, N.; Wong, K.H.; et al.
Abstract: Aims: Anaplastic thyroid cancer (ATC) is a rare but aggressive form of thyroid cancer with a median survival of 4 months. Recent advances in molecular profiling have shown that up to half of ATCs harbour the BRAF-V600E mutation. The aim of this study was to provide real-world data and experience on the use of combination therapy dabrafenib and trametinib in patients with BRAF-V600E-mutated advanced ATC. Materials and methods: We retrospectively evaluated patients with confirmed BRAF-V600E-mutated ATC, defined as patients with locally advanced or metastatic ATC with no locoregional, radical treatment options. Outcomes measured were overall survival, progression-free survival, response rate, discontinuation rate, dose reduction rate and toxicity data. Results: Seventeen patients were evaluated and the mean age was 68 years. Ten patients died by the time of censoring. The median duration of follow-up was 12 months (3–43 months). The estimated median overall survival was 6.9 months (95% confidence interval 2.46 months – upper confidence interval not reached) and the median progression-free survival was 4.7 months (95% confidence interval 1.4–7.8 months). Dose interruptions and/or reductions were common, but none of the patients had to permanently discontinue treatment because of toxicities. Severe toxicities (grades 3 and 4) were uncommon. Conclusions: This study supports the indication of dabrafenib and trametinib in BRAF-V600E-mutated ATC as an effective and well-tolerated treatment in an historically difficult to treat cancer. Highlights: Dabrafenib and trametinib increase survival of BRAF-mutant anaplastic thyroid cancer. Real-world data plug gaps in evidence in rare disease group. Largest cohort of real-world patient outcomes reported in the literature. Dabrafenib and trametinib combination is well-tolerated.